Impact of climate change on small-scale fishers and adaptation strategies in Bengkulu, Indonesia - Mulyasari Gita; Cahyadinata Indra; Irham (BIO Web of Conferences)
Climate change presents a significant global challenge for developing countries, especially Indonesia. However, this challenge also presents an opportunity for positive change, particularly in determining long-term investment decisions, including climate change adaptation and resilience measures. Uncertainty about future climate conditions makes the design of climate-supportive adaptive structures difficult and expensive, but it also opens the door for innovative solutions. This study reflects the perspective of small-scale fishers regarding the impacts of climate change and identifies the primary adaptation strategy. A survey was conducted in 700 small-scale fishery households to collect data on socioeconomic factors, climate change perceptions, and adaptation strategies. The research results show that 100% of small-scale fishers in the Bengkulu coastal area perceive climate change as harming their capture fisheries businesses. The level of adaptation carried out by small-scale fishers in the coastal regions of Bengkulu City could be significantly higher, as evidenced by the fact that only 15% of fishers have made efforts for climate change adaptation. Age, formal education, organizational membership, and access to climate information are crucial factors for adapting small-scale fishers to climate change. This research found that small-scale fisher’s awareness of climate change is deficient. Maximizing the use of fisher’s organizations and access to climate information can be helpful to climate change.